Determinants of Teacher Performance: Exploring the Role of Satisfaction and Motivation as Mediation - Acai Sudirman; Sherly Sherly; Vivi Candra; Edy Dharma; Darwin Lie (Jurnal Pendidikan dan Pengajaran, 2021)
This research aims to determine job satisfaction and motivation as mediating the relationship between teacher certification and principal supervision of teacher performance. The research design used a quantitative approach to causality. To obtain research data using documentation instruments and distributing questionnaires online. The sample used in the study was 215 respondents. The basis for determining the sample is oriented towards a non-probability sampling approach using a purposive sampling formula. To test the mediating effect of satisfaction and the relationship between principal supervision and compensation on teacher performance, the structural equation modeling (SEM) approach with partial least squares analysis is used. Following the research results, Teacher certification has a significant effect on satisfaction and motivation, and teacher certification has no significant effect on teacher performance. The results of subsequent research and the principal's supervision have a significant effect on job satisfaction, motivation, and teacher performance. Furthermore, the results showed that job satisfaction could not mediate the relationship between teacher certification and principal school supervision of teacher performance for the first and second mediation tests. Then, for the third and fourth mediation tests, results were obtained, which stated that motivation could not mediate the relationship between teacher certification and supervision of school principals on teacher performance. Therefore, principal supervision has a significant effect on job satisfaction, motivation, and teacher performance.